The Inverting Pyramid: Pension Systems Facing Demographic Challenges in Europe and Central Asia - Schwarz, AnitaM. (World Bank, 2015)
Pension systems in Europe and Central Asia are facing unprecedented demographic change. While many of the countries in the region have undertaken reforms when the economy faces difficult times, these reforms are frequently reversed when the economy improves. The demographic challenges that the region faces require a sustained effort toward changing the pension system toward something which provides adequate and sustainable benefits.